Compression of the respiratory tract in Fukuyama congenital muscular dystrophy. Issue 4 (19th June 2018) - Mitsutake, Akihiko; Matsumoto, Hideyuki; Hatano, Keiko; Hashida, Hideji
Abstract: We report the case of a 16‐year‐old boy in whom Fukuyama congenital muscular dystrophy (FCMD) had been genetically diagnosed. He required mechanical ventilation with tracheotomy due to the respiratory muscular weakness. Despite the respiratory supports, he subsequently had repeated temporal respiratory failure. Chest computed tomography revealed that the right main bronchus was compressed by the right clavicle and vertebra. An adjustable‐length and flexible tracheostomy tube and high positive end‐expiratory pressure were useful to keep the right bronchus patent. In FCMD, the respiratory tract may be occluded by severe scoliosis, which is improved by airway management.